Factorial study of compressive mechanical properties and primary in vitro osteoblast response of PHBV/PILA scaffolds - Sultana, Naznin (2012)
For bone tissue regeneration, composite scaffolds containing biodegradable polymers and nanosized osteoconductive bioceramics have been regarded as promising biomimetic systems. Polymer blends of poly(hydroxybutyrate-co-hydroxyvalerate) (PHBV) and poly(L-lactic acid) (PLLA) can be used as the polymer matrix to control the degradation rate. In order to render the scaffolds osteoconductive, nano-sized hydroxyapatite (nHA) particles can be incorporated into the polymer matrix. In the first part of this study, a factorial design approach to investigate the influence of materials on the initial compressive mechanical properties of the scaffolds was studied. In the second part, the protein adsorption behavior and the attachment and morphology of osteoblast-like cells (Saos-2) of the scaffolds in vitro were also studied. It was observed that nHA incorporated PHBV/PLLA composite scaffolds adsorbed more bovine serum albumin (BSA) protein than PHBV or PHBV/PLLA scaffolds. In vitro studies also revealed that the attachment of human osteoblastic cells (SaOS-2) was significantly higher in nHA incorporated PHBV/PLLA composite scaffolds. From the SEM micrographs of nHA incorporated PHBV/PLLA composite scaffolds seeded with SaOS-2 cells after a 7-day cell culture period, it was observed that the cells were well expanded and spread in all directions on the scaffolds